Die diaken in twee kerkordes in die Dordtse tradisie - Strauss, PJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
The deacon as prescribed in two church orders in the line of the order of Dordt The question is whether the church orders of the Christian Reformed Church in North America and the Dutch Reformed Church are in line with the church order of Dordt of 1619 on the character of the office of deacon in church. It is established that all three of them concentrate of the deacon as a ministry of mercy. These words are used by the order of the Christian Reformed Church, but also give a summary of the meaning of the other two church orders on the subject. A distinction is made between the focus of an office in church and the specific office as a practical means to achieve that focus. Die vraag is of die kerkordes van die Christian Reformed Church in North America en die Nederduitse Gereformeerde Kerk ten opsigte van hulle bepalings oor die aard van die diakenamp in die Dordtse tradisie of dieselfde lyn as die Dortse Kerkorde van 1619 beweeg? Die antwoord is dat al drie ordes na die bediening van die diaken as ’n diens van barmhartigheid verwys. Die Kerkorde van die Christian Reformed Church praat letterlik van hierdie diens as ’n “ministry of mercy”. ’n Onderskeid word getref tussen die fokus van ’n amp en die amp as die praktiese gestaltegewing daarvan.